Logit Modelling of Financial Behavior Among Young Adults: Evidence and Implications - Aeni, Ida Nur; Fithria, Annisa; Widiatami, Anna Kania (Dinamika Pendidikan, 2023)
This study aims to comprehensively uncover antecedents of the financial behavior of young adults in Indonesia. The financial behavior used in this study involved high-cost borrowing, emergency savings, and planning for retirement. Young adult has an opportunity to use financial products. Data have been collected from 86 young adults. Binary logistic regression has been applied to analyze the data through SPSS 23. The financial behavior of young adults depends upon objective and subjective financial literacy, self-control, and demographic variables such as marital status and a number of children. This study pays attention to young adults, bank, and non-bank financial institutions, and policymakers related to strategies for increased financial inclusion. The present paper attempts to comprehensively uncover the variables that help in cumulatively predicting the financial behavior of young adult.